2021
DOI: 10.1002/hep.31789
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of HBV PreS/S Mutations and the Effects of PreS2 Deletion on Mitochondria, Liver Fibrosis, and Cancer Development

Abstract: BaCKgRoUND aND aIMS: PreS mutants of HBV have been reported to be associated with HCC. We conducted a longitudinal study of the role of HBV preS mutations in the development of HCC, particularly in patients with chronic hepatitis B (CHB) having low HBV DNA or alanine aminotransferase (ALT) levels, and investigated the effects of secretion-defective preS2 deletion mutant (preS2ΔMT) on hepatocyte damage in vitro and liver fibrosis in vivo.appRoaCH aND ReSUltS: Association of preS mutations with HCC in 343 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“… 66 , 67 S‐gene mutations have been associated with HCC development, potentially because stop codons contribute to an accumulation of surface protein within hepatocytes. 68 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 66 , 67 S‐gene mutations have been associated with HCC development, potentially because stop codons contribute to an accumulation of surface protein within hepatocytes. 68 …”
Section: Discussionmentioning
confidence: 99%
“…66,67 S-gene mutations have been associated with HCC development, potentially because stop codons contribute to an accumulation of surface protein within hepatocytes. 68 While evidence is lacking for a mechanistic relationship between the presence of common RAMs such as M204I/V+L180M and HCC, an association has been reported. 9 It is possible that alterations in viral replicative capacity can underpin changes in pathogenicity, 8,9 but more work is required to determine the extent to which RAMs and VEMs may have functional significance in disease outcomes beyond that of drug or vaccine escape.…”
Section: Impact Of Rams/vems On Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The same study investigated the effects of the most common preS2 deletion in such patients (a short segment with 11 amino acids deleted in the preS2 region before proline). Huh7 cells expressing this preS2 mutated region had intracellular retention of HBsAg, which resulted in impairment of mitochondrial function, which in turn contributed to hepatocyte apoptosis, increased liver fibrosis and finally boosted the risk of HCC 53 . Beside the aspects related to HBV infection, the risk of HCC can be affected by metabolic factors and comorbidities.…”
Section: Three‐dimensional Carcinogenesis Related To Hbvmentioning
confidence: 99%
“…Studies have shown that type II GGH carrying PreS2-LHBS has a significant association with HCC, cirrhosis, and the decreased survival rate [12,13]. In addition, compared to wild-type LHBS, PreS2-LHBS shows higher ER retention that induces a substantial ER stress, leading to calcium accumulation, mitochondrial dysfunction, and genomic instability [14,15]. Notably, the PreS2 deletion region corresponded to the epitope of CD8 T cell, suggesting the immune-escape attribute of this mutant [11].…”
Section: Introductionmentioning
confidence: 99%